Pengembangan Kemandirian Anak Usia 5-6 Tahun di TK Dharmawanita Tunas Harapan - Malia Silranti (PG-PAUD Trunojoyo, 2019)
This study was aimed at describing development of the independence of children aged 5-6 year in  TK Dharmawanita Tunas Harapan kabupaten Pesisir Selatan. The research method is used  a qualitative descriptive. Thedata  were  gained  through  conducting  interviews,  observation  and  documentation.   The  data  were  then  analyzed using interactive model of data analysis from Miles and Huberman. The data was analyzed  by using triangulation  technique through collection data, reduction,  display, and verification. From the result research showed that development of independence refers to the curiculum. The learning method used by the teacher in developing independence is the method of habituation, conversing, question answer, playing and giving assignments. But in planning it is not clerly described the development of children’s independence.